'Best day since the bad germs came': Exploring changing experiences in and the value of coastal blue space during the COVID-19 pandemic, a Fylde Coast case study. Issue 1 (5th March 2022) - Earl, Joseph; Gormally-Sutton, Alexandra; Ilic, Suzana; James, Mike R
Blue spaces have long been associated with beneficially impacting human health and wellbeing. This article reflects upon the impact of the COVID-19 pandemic on people's experiences in coastal blue space and the health and wellbeing benefits derived from exposure to the space. Undertaken after the UK's first lockdown during Summer 2020, the work employed a qualitative mixed methods approach through a survey and interviews to provide an in-depth case study of people's experiences in and value of coastal blue space before and during the pandemic on the Fylde Coast in Lancashire. Findings show that participants valued the physical and mental health benefits derived from routine visits to coastal space, stimulated by emotional connections, a sense of escape and sensorial immersion. However, a busier coast in the lockdown's aftermath provoked a changed experience in coastal space for many participants due to a detachment from coastal space and the provoking of negative emotional experiences driven by heightened fears, reduced safety and increased litter. Mitigatory responses, through a changed coastal routine, and reflective responses, through a changed value of the coast, were found, the latter due to an increased appreciation of the health benefits from coastal exposure for some participants. Importantly, the findings highlight the need for coastal management to account for these experiences in protecting the health value of coastal space.